HUBUNGAN SISTEM PENGENDALIAN MANAJEMEN DAN PRESTASI PEMBIAYAAN BAGI HASIL: RESOURCE-BASED VIEW - Ataina Hudayati; Sofiah Md Auzair (Jurnal Ekonomi & Keuangan Islam, 2011)
Many Islamic economics as the basic concepts of Islamic banks, but the practice shows that the financing by buying and selling more practiced. The purpose of this study is to see the impact of performance measurement system as a management control system in improving organizational learning. The process of data collected by survey respondents RB field with Sharia and Islamic branches of Islamic banking in Indonesia. By analysis of partial least square, show an interactive performance measurement system is positively associated with organizational learning. This study also found that the quantity and quality of financing for the outcome positively related to achievement of financial and non financial BPRS, but only the quality of financing are related to the achievement of financial and non financial performance of Islamic bank branches.